Spinal Central Canal Dilation in MOG Antibody-Associated Disease Versus Other CNS Demyelinating Disorders. (5th December 2022) - Webb, Lauren; Cacciaguerra, Laura; Chen, John; Sechi, Elia; Redenbaugh, Vyanka; Dubey, Divyanshu; Pittock, Sean; Flanagan, Eoin
Abstract : Objective: To assess the frequency of spinal cord central canal dilation on magnetic resonance imaging (MRI) in patients with myelin-oligodendrocyte glycoprotein antibody-associated disease (MOGAD) myelitis compared to myelitis patients with aquaporin-4-positive-neuromyelitis optic spectrum disorder (AQP4+NMOSD) and multiple sclerosis (MS). Background: In MOGAD myelitis, a sagittal T2-hyperintense line accompanied by axial T2-signal restricted to the spinal cord gray matter forming an H-sign have been recognized and occur more frequently than in AQP4+NMOSD and MS myelitis. Pseudo-dilation of the ependymal canal has also been highlighted in cases of MOGAD myelitis, but detailed studies of this are lacking. Design/Methods: The spinal cord MRIs of myelitis patients with MOGAD (n = 63), AQP4+NMOSD (n = 37), and MS (n = 26) were evaluated for central canal dilation, defined as T2-hyperintensity with similar consistency to cerebrospinal fluid within a myelitis T2-lesion. Clinical data were collected from the medical record for MOGAD patients. The expanded disability status scale (EDSS) was used to quantify disability at nadir. Results: The median EDSS score at nadir for the MOGAD myelitis patients was 6 (range: 0-8). MOGAD patients experienced weakness (55/63[87%]), urinary retention/incontinence (50/63[79%]), numbness/paresthesias (48/63[76%]), and stool incontinence/constipation (36/63[57%]). Central canal dilation was more frequent in patients with MOGAD (23/63[37%]) than MS (0/26[0%]); p < 0.001) but did not differ from AQP4+NMOSD (14/37[38%]; p = 0.89). Spinal canal dilation resolved on follow-up axial MRI for most MOGAD (29/34[85%]) and AQP4+NMOSD (13/14[93%]) patients. Conclusions: Central canal dilation is a common radiologic accompaniment of acute MOGAD and AQP4+NMOSD myelitis, but not MS myelitis. The resolution of central canal dilation on follow-up MRI in most patients suggests it is transient and related to the acute inflammatory edema. Central canal dilation may differentiate MOGAD and AQP4+NMOSD from MS. Its recognition could facilitate earlier testing for MOG-IgG and AQP4-IgG, accurate diagnosis, and treatment.